Complete mitochondrial genome of Spanish flag snapper, Lutjanus carponotatus (Perciformes: Lutjanidae) - Gyungryul Kim; Ji-Hyun Lee; Md. Jobaidul Alam; Soo Rin Lee; Sapto Andriyono (Mitochondrial DNA. Part B. Resources, 2019)
The comple mitogenome of Spanish flag snapper, Lutjanus carponotatus was determined by next generation sequencing (NGS) technique. The mitogenome of L. carponotatus (16,514 bp) habors 37 genes (22 tRNAs, 2 rRNAs, 13 polypeptides) and two non-coding regions, the origin of light strand replication (OL) and the putative control region (D-Loop). Among the 37 genes in L. carponotatus mitogenome, 28 were encoded on the H-strand, whereas only 9 were on the L-strand. Phylogenetic relationship showed that the full mitochondrial genome sequences L. carponotatus was most closely related to Lutjanus russellii with 93% sequence identity clustering with Lutjanus fulviflamma (92%) and Lutjanus vitta (91%).